Pengaruh Model Pembelajaran Interaktif terhadap Motivasi Belajar Siswa Kelas 4 SD - Lita Wahyu Sinta Wati; Hartini Hartini; Melik Budyarti (Universitas PGRI Madiun, 2022)
This study aims to determine the effect of interactive learning models on the learning motivation of fourth grade students at SD 02 Pangongangan Madiun. This research is a quasi-experimental research with Nonequivalent Control Group Design. This research was conducted on students of class IV A as control and IV B as experimental class. The instrument in this study was a questionnaire of 22 intrinsic learning motivation items which were used as pretest and posttest for the control class and the experimental class. The data analysis technique in this study used the t-test. The results of this study indicate that the interactive learning model has an effect on students' learning motivation. It is proven by the results of hypothesis testing t arithmetic 5.454 > t table 2063 then Ho is rejected and Ha is accepted, so it can be seen that there is an effect of interactive learning model on learning motivation of fourth grade students at SD 02 Pangongangan.